The Impact of Electrical Power Interconnection Cooperation Between West Kalimantan and Sarawak in Increasing Economic Growth Potential in West Kalimantan - Herti, Riani Septi (Journal of Islamic World and Politics, 2020)
Electric power is a very important energy source for human life in fulfill the needs of lighting and production processes involving electronic and industrial goods. Indonesia is the country with the largest population in the Southeast Asia region. So, the demand for electricity also increases. The development of uneven electricity infrastructure in Indonesia has made some regions experience limited electrical power. Frequent interruptions and sharing the electric power, West Kalimantan is one of the provinces in Indonesia that still has electricity problems since 2006. Almost every day blackouts occur in a number of areas including Pontianak City and surrounding areas. In dealing with this problem, the efforts undertaken by the Government are conducting power interconnection cooperation with Sarawak, Malaysia which is geographically bordered directly with West Kalimantan through the ASEAN Power Grid program. In this study, the author will use a qualitative descriptive method, by clearly describing how the positive impact that given from the electric power interconnection between West Kalimantan and Sarawak in increasing economic growth potential in West Kalimantan.Keywords: Electric Power Interconnection, ASEAN Power Grid, West Kalimantan, Sarawak, Economic Growth Potential